Microcosms and field bioremediation studies of Perchloroethene (PCE) contaminated soil and groundwater - Ibbini, Jwan Hussein (Kansas State University, 2008)
Halogenated organic compounds have had widespread and massive applications in industry, agriculture, and private households, for example, as degreasing solvents, flame retardants and in polymer production. They are released to the environment through both anthropogenic and natural sources. The most common chlorinated solvents present as contaminants include tetrachloroethylene (PCE, perchloroethene), trichloroethene (TCE), trichloroethane (TCA), and carbon tetrachloride (CT). These chlorinated solvents are problematic because of their health hazards and persistence in the environment, threatening human and environmental health. This contribution provides insight on PCE degradation at laboratory and field scale at a former dry cleaning site in Manhattan, KS. Biostimulation experiments included combinations and concentrations of the following nutrients: soy oil methyl esters (SOME), yeast extract (YE), glucose, lactate, methanol and cheese whey. Bioaugmentation studies used KB-1 bacterial consortium (commercially available culture containing Dehalococcoides). This culture is known to complete the degradation of PCE to a safe end product, ethene. Concentrations of PCE and its degradation intermediates were monitored in the gas phase of the microcosm vials. Biostimulation of the natural ground water and soil microflora did not completely degrade PCE as cis-DCE (c-DCE) accumulated in the sample. Bioaugmented microcosms containing YE and SOME created reducing conditions for KB-1 culture, resulting in ~ 90% dechlorination of PCE to methane and c-DCE. Cheese whey microcosms containing 0.05% cheese whey inhibited the KB-1 culture. This inhibition was due to a drop of pH that inhibited the culture activity. Lower concentrations of cheese whey (e.g. 0.01% to 0.025%) reduced PCE and generated methane in KB-1 augmented microcosms. Based on microcosm results, a pilot bioremediation field study was conducted for a dry cleaning site contaminated with PCE. Ground water flow threatened public water wells located 1.5 miles from the source. Concentrations of PCE in the aquifer was 15 mg/L above the maximum contaminant level of 5 µg/L. Tracer studies with potassium bromide (KBr) were conducted before, during and after the bioremediation study. Nutrient solutions prepared with YE, SOME, lactate and glucose were used for biostimulation and preconditioning of ground water prior to KB-1 injection. Nutrients were provided twice during the pilot study to supplement microbial growth and cheese whey was used. During biostimulation no degradation beyond DCE was evident. The addition of KB-1 reduced PCE and DCE concentrations in the monitoring wells of the pilot study area. Total chlorinated ethene concentrations did not reach background levels 2 years after the last nutrient addition. Tracer results showed that microbial growth decreased ground water velocity during the study, but returned to normal conditions 1 year after the last nutrient addition. In this study we were able to show that native microbial population was not able to degrade PCE to final end products. Therefore, it was necessary to introduce KB-1 culture a long with nutrients to support complete reductive dechlorination of PCE.
Keywords: Perchloroethene; Bioremediation; KB-1; Microcosms; Biogeochemistry (0425); Biology, Microbiology (0410); Chemistry, Biochemistry (0487)